Reduction of Involuntary Admissions in Patients With Severe Psychotic Disorders Treated in the ACCESS Integrated Care Model Including Therapeutic Assertive Community Treatment - Schöttle, Daniel; Ruppelt, Friederike; Schimmelmann, Benno G.; Karow, Anne; Bussopulos, Alexandra; Gallinat, Jürgen; Wiedemann, Klaus; Luedecke, Daniel; Rohenkohl, Anja Christine; Huber, Christian G.; Bock, Thomas; Lambert, Martin (Frontiers in Psychiatry, 2019)
Objective: The ACCESS treatment model offers assertive community treatment (ACT) embedded in an integrated care program to patients with severe psychotic disorders. Compared to standard care, it proved to be more effective in terms of service disengagement and other outcomes in patients with psychotic disorders over 12, 24 and 48 months. Many patients with severe mental disorders experience involuntary admissions which can be potentially traumatic. In this study, we assessed the effect of ACT on reducing involuntary admissions over an observation period of 4 years. Method: 171 patients treated in ACCESS were included in this study. The primary outcome was rate of involuntary admissions during 48 months. Secondary outcomes were differences between those with and without involuntary admissions in the two years prior to ACCESS regarding change of psychopathology, severity of illness, psychosocial functioning, quality of life, satisfaction with care, medication non-adherence, and service-disengagement. Results: Of 171 patients, 58 patients (33.9%) were involuntarily admitted to hospital in the past 2 years before entry. During the four years of treatment, 16 patients (9.4%) were involuntarily admitted to hospital which was a significantly lower rate compared to the two years before inclusion in ACCESS (p<.001). Comparing the two groups, larger improvements in severity of illness (p = .004) and functional status (p = .043) were detected in the group with no history of involuntary admissions. At four-year follow-up, of the remaining patients 69.2% (n=81) were full adherent (p < .001), compared to 18.9% (n = 31) at baseline with no differences between the two groups over the study period (p=.25). Over four years, only 13 patients (13.2 %) were service-disengaged due to non-practical reasons. Conclusions: In this long-term study, we were able to demonstrate a reduction in involuntary admissions in four treatment years compared to the two years prior to admission to the ACCESS-model in patients with severe and mostly multiphase schizophrenia spectrum disorders and affective disorders with psychotic features. This may help prevent patients from suffering from a potentially traumatic experience during treatment in the psychiatric system.